Baseline studies on sex-disaggregated statistics of members and gender roles of officers among recognized UPLB student organizations - Lado, Jickerson P.; Miranda, Marcelina C.; Abriol-Santos, Katrina Joy M.; Hagosojos, Charlotte H.; Casquete, Jimby E.; Mojica, Marites E.; Cadiz, Nina M. (2021)
The sex-disaggregated statistics of members of recognized UPLB students organizations for five academic years were determined. Furthermore, the prevailing gender roles in elected key positions were identified. This is the first attempt to create and profile recognized UPLB student organizations in terms of sex-disaggregated data (SDD) that could translate to effective policies and campaign strategies to enable harmonized and gender-sensitive culture in UPLB. Is sought to identify and assess the SDD of members among recognized UPLB student organizations using both qualitative and quantitative method of analysis. In a preliminary study, the data submitted by an average of 170 recognized organized for the past five years (2012-2016) was consolidated. Data from the Office of Student Affairs Management (OSAM) System was also utilized. Furthermore, a Focus Group Discussion (FGD) was employed for selected student organizations. Participants were either heads/ officers of their respective organizations or members who are also knowledgeable of their constitutions, by-laws, and policies. The SDD revealed that there were 20% more female members than male members in student organizations in general. This was validated by higher enrollment frequency count of females than males for years 2012-2016. Interestingly, the female-dominated membership pattern was not observed across all types of students organizations. In contrary, sports and recreation and political organizations were male-dominated. Campaign strategies to encourage females to be part of these organizations are highly recommended. Through there are no written rules in terms of sex preference for activity leadership and role assignment, the study revealed that student organizations tend to associate presidency and other rigorous, physically-demanding tasks to male members and the vice president (membership committee), secretary, and treasurer positions-those that require managerial skills and finesse-to female members. Student organizations are highly recommended to undergo gender sensitivity training and other gender-related activities under the facilitation of the Student Organization and Activities Division (SOAD) and supervision of the UPLB Gender Center to create awareness and promote gender-empowering culture.
Keywords: Gender role; Leadership